An integrated network pharmacology and molecular modelling study of phytoconstituents targeting Alzheimer's disease - Saumya Khanna; Divakar Selvaraj; Mehak Tyagi; Devadharshini; Saravanan Jayaram (Medicine in Omics, 2024)
The present study involves the use of combined network pharmacology and molecular modelling approach for identifying important phytoconstituents that could modulate the functions of multiple therapeutic targets in Alzheimer’s disease. A list of botanicals reported in the literature for their efficacy in Alzheimer’s disease, the phytochemicals present in the botanicals were identified with the help of network pharmacology approach. The pharmacokinetic properties like blood brain barrier penetration and Lipinski’s rule of five for the selected phytoconstituents were analyzed. The major targets involved in the pathogenesis of Alzheimer’s disease were collected from the DisGeNET database. The selected proteins were subjected to topological analysis using Cytoscape software to identify the important targets in the network. The top 7 phytoconstituents and 5 proteins were subjected to molecular docking, MM-GBSA and molecular dynamics studies. A total of 15 plants and 1443 phytoconstituents were identified through a literature survey and from several databases. The pharmacokinetics study revealed that 7 phytoconstituents - glycyrrhisoflavone, eugenol, ferulic acid, methyl jasmonate, geranyl formate, formononetin, and elemicin- exhibited favourable pharmacokinetic properties. Five targets, HMOX1, CNR1, STAT3, HDAC2, and MAOB were found to be important in the network of 3300 proteins based on degree centrality and betweenness centrality. Among the seven phytoconstituents, glycyrrhisoflavone exhibited good dock scores and free energy value. Based on this, the stability of glycyrrhisoflavone with the five selected targets were analyzed using molecular dynamics study. Glycyrrhisoflavone showed good stability with most of the selected therapeutic targets. The current study reveals that the selected phytoconstituents i.e glycyrrhisoflavone, eugenol, ferulic acid, methyl jasmonate, geranyl formate, formononetin, and elemicin could serve as good lead molecules in treatment and management of Alzheimer’s disease through modulation of multiple targets.